Epidemiology of opportunistic fungal infections in Latin America (2010)
ABSTRACT: This review discusses the epidemiology of the most clinically relevant opportunistic fungal infections in Latin America, including candidiasis, cryptococcosis, trichosporonosis, aspergillosis, and fusariosis. The epidemiologic features, including incidence, of some of these mycoses are markedly different in Latin America than they are in other parts of the world. The most consistent epidemiologic data are available for candidemia, with a large prospective study in Brazil reporting an incidence that is 3- to 15-fold higher than that reported in studies from North America and Europe. Species distribution also differs: in Latin America, the most common Candida species (other than Candida albicans) causing bloodstream infections are Candida parapsilosis or Candida tropicalis, rather than Candida glabrata.